A comparative study of postoperative acidemia after intraoperative administration of balanced crystalloid (Plasma-lyte A@) versus 0.9% sodium chloride in gastrointestinal surgery - Laxmi Narayan Dash; Jagannath Panda; Shibanee Jena; Harikrishna Dalai; Pritish Chandan Sahu; Debadas Biswal (Asian Journal of Medical Sciences, 2024)
Background: The administration of intravenous fluids is one of the most common and universal interventions in medicine. Fluid therapy is the most challenging and debated aspect of perioperative care. Plasma-lyte A® Injection (multiple electrolytes injection, type 1, USP) is indicated as a source of water and electrolytes or as an alkalinizing agent. 0.9% sodium chloride is an isotonic crystalloid solution having a sodium concentration higher is useful in replacing fluid and electrolyte loss.